EVALUATION OF VILLAGE FUND USE BASED ON CHANGES TO THE VILLAGE BUDGET - Zakia Fikra; Anisa Br Tarigan; Rinayanti; Lisa Amelia; Adya Raziq; Syawal Harianto (PT. Radja Intercontinental Publishing, 2025)
This study aims to evaluate the utilization of Village Funds based on changes in the Village Budget (APBDes) over a three-year fiscal period. The analysis focuses on the dynamics of budget adjustments, patterns of reallocation, and policy directions that reflect the village government's response to evolving social, economic, and regulatory conditions. Using a literature review method, this study integrates APBDes data with various scholarly sources to present a comprehensive understanding of the effectiveness, efficiency, and alignment of fund utilization with development priorities. The findings indicate that each fiscal year exhibits distinct patterns of budget change, reflecting the village government's adaptive capacity in managing public finances flexibly and in accordance with community needs. These insights contribute to the broader understanding of village financial governance and offer recommendations for improving planning processes, transparency, and accountability in budget management.